Terahertz frequency electromagnon and magnon modes in multiferroic cupric oxide - Jones, S; Gaw, S; Prabhakaran, D; Boothroyd, A; Lloyd-Hughes, J; IEEE (2013)
We examined the terahertz magnetoelectric response of cupric oxide, a high-temperature multiferroic with a cycloidal spin structure that induces an electrical polarisation. Terahertz time-domain spectroscopy at various temperatures and magnetic fields uncovered electromagnon and magnon modes, providing insights into the spin Hamiltonian. © 2013 IEEE.